Impromptu: great impromptu speaking is never just impromptu - Ramlah A. Nawi; Burhanuddin Yasin; Ibrahim C. R. Champion (Universitas Syiah Kuala, 2015)
Great impromptu speaking, reciting and singing are never just an isolated impromptu act. It is the result of endless practice to perfect performance that can then be given impromptu. One of the main objectives of learning English as a Second Language (ESL) is to be able to speak English impromptu, not just on the stage or in front of an audience but also in a casual meeting, on the street or during a formal meeting in a board-room. In fact to be able to speak “impromptu” should be the Holy Grail of teaching and learning ESL, more important than reading, writing and listening. So how come it is not given the priority it deserves – and how come it seems such a difficult goal? We believe it is because teachers and learners neglect to emphasize and practice the key to learning impromptu speaking. That key we believe is practice, practice and more practice. We can remember songs from our kindergarten years and we can still sing them because we practiced, practiced and practiced them. We believe that the teaching of ESL often overlooks the critical importance of lots of practice to create depth of learning and that creative methods of practicing need to be taught and practiced in ESL courses until such methods become deeply habitual, in fact they become a new personal paradigm. If our students aim to become great at ESL, they, too, must take continuous never-ending practice to heart.